Direct democracy and local public goods evidence from a field experiment in Indonesia - Olken, Benjamin A. (Working paper series / National Bureau of Economic Research, 2008)
"This paper presents an experiment where 48 Indonesian villages were randomly assigned to choose development projects through either representative-based meetings or direct election-based plebiscites. Plebiscites resulted in dramatically higher satisfaction among villagers, increased knowledge about the project, greater perceived benefits, and higher reported willingness to contribute. Changing the political mechanism had much smaller effects on the actual projects selected, with some evidence that plebiscites resulted in projects chosen by women being located in poorer areas. The results show that direct participation in political decision making can substantially increase satisfaction and legitimacy, even when it has little effect on actual decisions"--National Bureau of Economic Research web site